In vitro antimicrobial activity of mexican plants on bovine mastitis bacteria: preliminary studies (Bioscience Journal, 2020)
The present study aimed to evaluate the efficacy of traditionally used antibacterial plants (Euphorbia prostrata, Schinus molle, Brickellia veronicaefolia and Lepidium virginicum) in Santa Rosa Range in Guanajuato against major mastitis-causing pathogens. The selected plants were phytochemically screened for alkaloids, flavonoids, polyphenols, saponins, anthraquinone, cardiac glycosides, steroids and terpenoids. Moreover, to achieve the main purpose of the present research, extracts of selected plants were tested for in vitro antibacterial activity against Staphylococcus aureus, Escherichia coli, Shigella spp., Bacillus subtilis, Clavibacter spp., Proteus vulgaris and Salmonella spp. All these bacterial were isolated from clinical mastitis in dairy cows. The results indicated that the ethanolic extract of the aerial part of L. virginicum exhibited the strongest antimicrobial activity, and it could be potential candidate specie for the development of novel veterinary drugs with low cost and fewer side effects.